Growth, development and yield of potatoes - Khurana, Subhash Chander (1981)
Experiments were conducted in growth rooms to study the photoperiodic response of Pentland Crown. In field experiments the effects of sprouting techniques and the possibility of mixing of different physiologically aged tubers and the use of plant growth regulator, pp333 were studied. Sprout growth of the tubers used for planting was studied during storage. Light interception in the photo-synthetically active range (PAR), was measured in the crop canopies. Relevant literature relating to the present investigation was briefly reviewed.